2021
DOI: 10.2463/mrms.mp.2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Distribution of Intravenously Administered Gadolinium-based Contrast Agent over a Period of 24 Hours: Evaluation with 3D-real IR Imaging and MR Fingerprinting

Abstract: Purpose: To evaluate the feasibility for the detection of slight contrast effects after intravenous administration of single dose gadolinium-based contrast agent (IV-SD-GBCA), the time course of the GBCA distribution up to 24 h was examined in various fluid spaces and brain parenchyma using 3D-real IR imaging and MR fingerprinting (MRF). Methods:Twenty-four patients with a suspicion of endolymphatic hydrops were scanned at pre-administration and at 10 min, 4 and 24 h post-IV-SD-GBCA. 3D-real IR images and MRF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
(92 reference statements)
2
16
0
Order By: Relevance
“…However, the intrathecal administration of GBCA in humans has not been approved in any country [36]. In this context, several trials have evaluated the glymphatic function through the intravenous administration of GBCA [37][38][39][40][41]. In contrast to the tracer study, including intravenous GBCA, provides information about the tracer's movement as the integral of the elapsed time, and the diffusion method provides information about the tissue water molecules at the moment the MPGs are applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intrathecal administration of GBCA in humans has not been approved in any country [36]. In this context, several trials have evaluated the glymphatic function through the intravenous administration of GBCA [37][38][39][40][41]. In contrast to the tracer study, including intravenous GBCA, provides information about the tracer's movement as the integral of the elapsed time, and the diffusion method provides information about the tissue water molecules at the moment the MPGs are applied.…”
Section: Discussionmentioning
confidence: 99%
“…3D-real IR imaging is more sensitive than MR fingerprinting to extremely low concentrations of GBCA in fluid. 85 The longitudinal assessment of 3D-real IR images after the intravenous administration of GBCA can help analyze the morphological microstructure of the downstream region and understand the relationship with glymphatic system function. Furthermore, the degree of leakage of GBCA from the subpial space around the cortical veins to the surrounding subarachnoid space observed after intravenous administration of GBCA was shown to be significantly accelerated by aging 86,87 (Fig.…”
Section: Intravenous Administration Of Gbcamentioning
confidence: 99%
“…Meanwhile, it is important in the study of the glymphatic system to elucidate the detailed anatomy of the connections from the perivenous space around the veins in the brain, to the subpial space around the cortical veins, and finally, to meningeal lymphatic vessels. [84][85][86][87] Also, it is crucial to reveal the relationship between cyst formation in the vicinity of these connections and the stagnation of ISF flow. 90 These studies will help us to understand the glymphatic system and the kinetics of drugs in the CNS.…”
Section: Mri Of Glymphatic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Several minutes after intravenous administration (IV) of a gadolinium-based contrast agent (GBCA), the subpial space around the cortical veins is enhanced in human patients. 1,2 In addition, it has been shown that the GBCA often leaks into the surrounding subarachnoid space by 4 hrs after intravenous administration. [3][4][5] It has also been reported that leakage of the GBCA into the subarachnoid space around the cortical veins on 3D real inversion recovery (3D-real IR) images obtained at 4 hrs post-administration is observed frequently in subjects over 37 years of age, but significantly less often in individuals younger than 37 years 3,4 A potential connection between the subpial space around the cortical veins and the presumed meningeal lymphatic vessels on both sides of the superior sagittal sinus [6][7][8] has been reported using MR imaging.…”
Section: Introductionmentioning
confidence: 99%